2008
DOI: 10.1038/sc.2008.10
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive assessment of lower extremity muscle composition after incomplete spinal cord injury

Abstract: Study Design: Cross-sectional study. Objective: (1) To quantify intramyocellular lipid (IMCL) content of the soleus muscle. (2) To assess the T 2 relaxation rates in the lower extremity skeletal muscles in persons with incomplete spinal cord injury (SCI). Setting: Academic Institution, Florida. Methods: Eight subjects (42 ± 10 years old; 70 ± 12 kg; 176 ± 10 cm) with chronic (17 ± 9 months post injury) motor SCI (C4-T12; ASIA C or D) and eight matched healthy controls were tested. Localized unsuppressed proton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 20 publications
2
20
0
2
Order By: Relevance
“…In the SCI + IMM group, the addition of cast immobilization minimized the loading on the muscle, allowing for examination of the role of neuromuscular activity and/or loading in the muscle adaptations after SCI. This model is more consistent with what is generally observed in human complete or chronic incomplete SCI, [39][40][41][42] in which patients usually experience an extended period of bed rest and reduced activity during the acute phase of the injury, up to several weeks. The primary muscles of ambulation continue to experience reduced loading for several weeks to months after SCI as activity-based rehabilitation is delayed by other posttraumatic complications.…”
supporting
confidence: 75%
“…In the SCI + IMM group, the addition of cast immobilization minimized the loading on the muscle, allowing for examination of the role of neuromuscular activity and/or loading in the muscle adaptations after SCI. This model is more consistent with what is generally observed in human complete or chronic incomplete SCI, [39][40][41][42] in which patients usually experience an extended period of bed rest and reduced activity during the acute phase of the injury, up to several weeks. The primary muscles of ambulation continue to experience reduced loading for several weeks to months after SCI as activity-based rehabilitation is delayed by other posttraumatic complications.…”
supporting
confidence: 75%
“…Using nuclear magnetic resonance, previous studies have reported increased intramuscular lipid content in deconditioned leg muscles of PAR individuals (21,23,55). In addition, an initial reduction of muscle mitochondrial oxidative activity has been observed directly after spinal cord injury, followed by a recovery to nearly normal levels after 6 mo (13).…”
mentioning
confidence: 95%
“…The ability to monitor in vivo spectral changes has a range of clinical applications for the musculoskeletal system, including monitoring intracellular and extracellular fat changes, 31 exercise-induced changes in metabolites, 14 intracellular pH abnormalities in chronic fatigue syndrome, 22 and examining muscular response to neurological insult and/or disuse through intramyocellular lipid content 33 or changes in inorganic phosphate. 26,27 SPATIAL ENCODING I n addition to chemical information, the signal can be encoded with spatial position and used to obtain an image.…”
Section: Key Pointsmentioning
confidence: 99%